Trust as a key element in family mediation during divorce: strategies, practices (supervision experience with the use of neural networks) - V. V. Krivopuskov; I. V. Mkrtumova; O. E. Gracheva (Цифровая социология)
The article summarises the experiment on building confidence in the procedure of family mediation – peaceful resolution of family disputes through introduction of the technology of the first outreach meeting. The article analyses the statistics of marriage and family relations, the number of divorces in Russia, Moscow, in the world for 5 years, also during the COVID-19 pandemic. In addition, the work examines the statistics of enforcement proceedings on family relations and the order of communication for several years as well as sociological studies of 2022–2023. The results of experimental supervision using technologies of two neural networks are presented. The peculiarities of family mediation as the most effective non-judicial way of resolving family disputes are studied. It is shown that the achievement of the result, peaceful settlement of family disputes, was facilitated by the experimental development and implementation of a new procedure for Russia – first outreach meeting. It was performed by the Centre for mediation and socio-legal assistance, jointly with the Departments of Social Protection of population of Moscow. The first results are presented: 98 % of efficiency, almost all couples gave their consent to mediation, and the first mediations were successfully conducted. Some of the main reasons for low prevalence of pre-trial settlement of family conflicts were revealed: the normative non-mandatory nature of family mediation for couples with minor children when filing for divorce and lack of awareness of couples about advantages and benefits of resorting to family mediation. The research presents arguments proving that the first outreach meeting is a successful strategy of trust building and the first step to mediation and to preservation of family, family identity, spiritual values for their further transmission to the next generation in the continuous chain of socio-cultural identity